Pergerakan Harga Saham Syariah Pada Saham Bank Syariah Di lihat Dari Faktor Makroekonomi - Muharrami, Rais Sani; Zahidah, Shufiatul; Yoga, Ika (BISNIS, 2017)
This study aims to determine the macroeconomic indicators that affect sharia banking stock price index period 2014-2016. Four variables consist of inflation, BI interest rate, rupiah exchange rate and SBIS are considered to have an effect on the syariah bank stock price index. This research uses quantitative method. This study uses monthly time series data which is analyzed by multiple linear regression. The data used are secondary data with 36 data from January 2014-December 2016. Data collection is taken with documentation techniques sourced from the official website of Bank Indonesia and yahoofinance.com. The results showed that inflation did not significantly influence the sharia bank stock price index. While the BI interest rate, the exchange rate of rupiah and SBIS have a significant influence on PT Bank Panin Dubai Syariah Tbk stock price index. From the results of this study, it can be concluded that the indicators considered in the PT Bank Panin Dubai Syariah Tbk stock price index are BI rate, rupiah exchange rate and SBIS.